On Their Shoulders: A Discussion of the Foundational Nature of Female Pioneers of Chinese Medicine in the United States - Marnae C. Ergil; Claudia Citkovitz; Belinda Anderson; Sally Rappeport; Claire Cassidy (Chinese Medicine and Culture, 2026)
Abstract: In the United States, women constitute a clear majority of practitioners and students of Chinese Medicine (CM), yet leadership visibility has often appeared disproportionately male. This paper examines women’s contributions to the development and professionalization of CM in the US over the past five decades. It documents female leadership across two broad domains: (1) intellectual and institutional foundations including: academic scholarship, translation, clinical research and clinical integration, and (2) practice-based leadership: including pioneering licensure efforts, professional governance and education, clinical authorship, and business infrastructure. Through focused discussions and overview tables, we demonstrate that women have shaped the field not only demographically but structurally. Their work has defined terminology, advanced research, built educational institutions, founded professional organizations, authored foundational texts, and developed the regulatory and economic frameworks that sustain the profession. Often operating within collaborative networks rather than singular authority roles, women’s contributions have been embedded in the profession’s architecture itself. This selective but foundational mapping reframes the historical narrative of US CM and invites further systematic documentation of female leadership within the field.